Research on Coordinated Relationship Between Deformation and Force in Shaft Foundation Pit Support Structures - Chuanzhao Xu; Jian Hou; Bingfeng Liu; Fangchao Lei; Li Song (Buildings, 2024)
In order to investigate the coordinated relationship between lateral deformation of the diaphragm wall and axial force of the internal strut, this paper first carried out a scaled model test on the mechanical features of a foundation pit support system based on a novel axial force servo device. Then, a finite element model was established to simulate the scaled model test, and the correctness of the finite element modeling approach was validated by comparing test results. After that, the same finite element modeling method was used to analyze the coordinated relationship between axial force and lateral deformation in the prototype foundation pit support structure. The results show that the axial force of the inner strut is negatively correlated with the lateral deformation in the diaphragm wall. The initial maximum lateral deformation in the diaphragm wall of the shaft foundation pit occurs at the bottom of the foundation pit, so changing the length of bottom strut simultaneously is the most effective way to adjust the mechanical behavior of the support structure. Under various support conditions, the maximum lateral deformation of the diaphragm wall in the prototype project is 0.59~0.66‰ of the total excavation depth of the foundation pit, and the maximum axial force of internal support is 11~30% of the yield load of a single steel strut.